Association between ACTN3 gene polymorphism and muscle strength in older adults - Kłoska, Sylwester; Marciniak, Anna; Woźniak, Marcin; Perkowski, Radosław; Podhorecka, Marta; Gębka, Dominika; Androsiuk-Perkowska, Joanna; Kujawski, Sławomir; Kożuchowski, Marcin; Kozłowski, Henryk; Kędziora-Kornatowska, Kornelia; Zukow, Walery (Journal of Education, Health and Sport, 2018)
The decrease of muscle strength and general physical fitness is a big problem in the elderly group. It often prevents the proper functioning of a person, which makes him/her dependent on caretakers. It is believed that the some polymorphisms in ACTN3 geneare associated with better results in strength sports. If those polymorphisms affect muscle strength, they may also be related to the health condition of older people. Our study was conducted on a group of 60 people over 60 years of age. The relationship between overall fitness and muscular strength of elderly patients with ACTN R577X gene polymorphism was checked. The ACTN3 gene was tested by PCR-RFLP. Overall fitness was tested using the IPAQ questionnaire and fitness tests: Tinetti, DGI, Up&Go, SPPB, standing on one leg (both right and left). Based on the results of the survey, the MET and BMI coefficients were determined. It was found that the RX genotype is associated with better results achieved in the SPPB test. Genotype XX was associated with worse results in the right leg standing test (p<0.05). The R-allele of the ACTN3 gene wasassociated with better results obtained during the standing test on the right leg (p<0.05).Based on obtained results it was impossible to determine a clear impact of the ACTN3 gene on muscle strength and health of the older adults.